Dialoghi tra sguardi: Johari Window e comunicazione interculturale (Altre Modernità, 2015)
This study aims at investigating some issues of intercultural communication, underlining how the Johari Window scheme may be a useful tool to observe, understand and improve interpersonal relations, especially in a multicultural group. Particular attention is given to the problems which may interfere in corporate work teams, since communication is fundamental for a company: both for its economic goals and for the human resources management.The present analysis focuses on some verbal aspects of communication, with an intercultural comparative approach between English – generally speaking, lingua franca of international business – and other languages (Victor 1992, Castiglioni 2011).Yet language is not the only way to communicate: values and non-verbal aspects can intervene in every communicative act (Balboni 2007, Watzlawick 1971), changing our perceptions and expectations. Often, what we consider as natural, is actually cultural, and therefore variable. These differences can generate serious misunderstandings, particularly at work.The Johari Window method, suggested by Luft (1997), is based on increasing and sharing information between ourselves and the others, in order to improve interior awareness, relations, and effectiveness. For this reason, it is a useful means for helping intercultural dialogue.